2019
DOI: 10.5194/aab-62-59-2019
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation pattern of the goat <i>PITX1</i> gene and its effects on milk performance

Abstract: Abstract. Paired-like homeodomain transcription factor 1 (PITX1) is a pivotal gene in the hypothalamic–pituitary–adrenal axis, which is a well-known pathway affecting lactation performance. The aim of this study was to analyze the DNA methylation profile of the PITX1 gene and its relevance to milk performance in Xinong Saanen dairy goats; thus, potential epigenetic markers of lactation performance were identified. A total of 267 goat blood samples were divided into “low” and “high” groups according to two milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It is well known that the biological mechanisms of quantitative traits are very complicated, and the present study is only based on SNP data analysis. Some studies have shown that copy number variation and DNA methylation are also related to milk production and quality traits [55][56][57]. The SNP (1.192 kg; p = 1.57 × 10 −8 ) on BTA5 is associated with an increase of PY and it is also within the previously reported QTL region, which is associated with milk fatty acid content.…”
Section: Gwas For Milk Traitsmentioning
confidence: 69%
“…It is well known that the biological mechanisms of quantitative traits are very complicated, and the present study is only based on SNP data analysis. Some studies have shown that copy number variation and DNA methylation are also related to milk production and quality traits [55][56][57]. The SNP (1.192 kg; p = 1.57 × 10 −8 ) on BTA5 is associated with an increase of PY and it is also within the previously reported QTL region, which is associated with milk fatty acid content.…”
Section: Gwas For Milk Traitsmentioning
confidence: 69%
“…After cells were stimulated with the exogenous additive, they might respond to stimulation initially by interferon produced by STAT1-mediated immune response ( 39 , 40 ). Whereas, BACH2 is a regulator of fatty acid profiles in mammary gland ( 41 ), CTCF regulates the localization of adhesin protein ( 42 ), and NFIB regulates the formation of alveolar epithelium via the Hippo signaling pathway ( 43 , 44 ). These findings stated that the regulation of TFs is essential for GM-preadipocyte transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that GRPR gene may affect milk fat through the calcium signaling pathway. Because of the complexity of the biological mechanisms of quantitative traits, the study is only based on SNP data, many studies showed that copy number variation and DNA methylation are also associated with milk performance[4042], The PY-associated SNP on BTA5 is within previously reported QTL region, which is associated with milk fatty acid content, this SNP is in the SLCO1A2 gene, which is encoding solute carrier anion transporter family, member 1A2, the gene participate in digestive system, organic anion transport process and bile secretion pathway (KEGG: 04976). Furthermore, when the association model not fitted PCs as covariance, four SNPs are overlapped with model with fitted PCs:rs109875012 ( ZNF384 ), rs136949224 ( SCARA5 ), rs109421300 ( DGAT1 ), and rs109528658 ( EP400 ), it is suggested that these significant SNPs could more stable and reliable.…”
Section: Discussionmentioning
confidence: 99%